(untitled) (Revista de Ciências Agroveterinárias, 2015)
In recent years, uremic toxins have been widely investigated as an immunosuppressive factor for nephropathic patients. This study aimed to test the hypothesis that, as it was similarly observed in humans, the rate of apoptosis and superoxide production in polymorphonuclear leukocytes are changed in dogs treated with uremic serum. The superoxide production of polymorphonuclear leukocytes and apoptotic index of 10 healthy dogs incubated with autologous and homologous serum from healthy and uremic dogs was compared. Thus, there was an effect of partial inhibition of oxidative metabolism in uremia without correlation with the acceleration of polymorphonuclear leukocytes apoptosis in dogs.